PENGARUH IKLAN INSTAGRAM DAN TIKTOK TERHADAP EKSISTENSI PELANGGAN KULINER DI MASA PANDEMI COVID-19 DI YOGYAKARTA - Winarni, Selo (PRIMA EKONOMIKA, 2021)
Indonesian economy deteriorates due to recent COVID-19 pandemic, this hugely affect many economic sector, for example tourism and culinary. But, culinary sector seems to escalate in new normal era. This research aim to observe the impact of advertisement's newest form, which is done through Instagram and TikTok app to Customer Existence in Yogyakarta city culinary section. Data collection for this research use questionnaire, and the analysis done using multiple regression with SPSS program. As much as 30 culinary businesses owner taken as sample. For instrumental testing purpose, researcher use validity and reliability test, also T test, F test and adjusted R Squared is observed to test the hypothesis. Result indicated by this research showed that advertisement done through Instagram (X1) and TikTok (X2) partially has a positive impact to Customer Existence on culinary business in Yogyakarta city, especially during these pandemic periods. Outcome of this research hopefully could be used as reference, mainly for people who seek on how to preserve their business in Yogyakarta. Keywords : Customer Exixtence. Instagram. TikTok